Microdosing and standard‐dosing take‐home buprenorphine from the emergency department: A feasibility study. Issue 6 (20th October 2020) - Moe, Jessica; Badke, Katherin; Pratt, Megan; Cho, Raymond Y; Azar, Pouya; Flemming, Heather; Sutherland, K. Anne; Harvey, Barbara; Gurney, Lara; Lockington, Julie; Brasher, Penny; Gill, Sam; et al.
Abstract: Objective: Emergency department (ED)–initiated buprenorphine may prevent overdose. Microdosing is a novel approach that does not require withdrawal, which can be a barrier to standard inductions. We aimed to evaluate the feasibility of an ED‐initiated buprenorphine/naloxone program providing standard‐dosing and microdosing take‐home packages and of randomizing patients to either intervention. Methods: We broadly screened patients ≥18 years old for opioid use disorder at a large, urban ED. In a first phase, we provided consecutive patients with 3‐day standard‐dosing packages, and then we provided a subsequent group with 6‐day microdosing packages. In a second phase, we randomized patients to standard dosing or microdosing. We attempted 7‐day telephone follow‐ups and 30‐day in‐person community follow‐ups. The primary feasibility outcome was number of patients enrolled and accepting randomization. Secondary outcomes were numbers screened, follow‐up rates, and 30‐day opioid agonist therapy retention. Results: We screened 3954 ED patients and identified 94 with opioid use disorders. Of the patients, 26 (27.7%) declined participation: 10 identified a negative prior experience with buprenorphine/naloxone as the reason, 5 specifically cited precipitated withdrawal, and none cited randomization. We enrolled 68 patients. A total of 14 left the ED against medical advice, 8 were excluded post‐enrollment, 21 received standard dosing, and 25 received microdosing. The 7‐day and 30‐day follow‐up rates were 9/46 (19.6%) and 15/46 (32.6%), respectively. At least 5/21 (23.8%) provided standard dosing and 8/25 (32.0%) provided microdosing remained on opioid agonist therapy at 30 days. Conclusions: ED‐initiated take‐home standard‐dosing and microdosing buprenorphine/naloxone programs are feasible, and a randomized controlled trial would be acceptable to our target population.